Chemotherapy patient perception regarding communication with the healthcare staff - Bittencourt Romeiro, Fernanda; Peuker, Ana Carolina; Bianchini, Daniela; Kern de Castro, Elisa (Psicooncología, 2016)
Purpose: To qualitatively explore the communication between healthcare professionals and oncology patients based on the perception of patients undergoing chemotherapy. Method: Qualitative and exploratory design. Participants were 14 adult patients undergoing chemotherapy at different stages of the disease. A socio-demographic and clinical data form was utilized along with semi-structured interviews. The interviews were audio-recorded, transcribed and content analysis was performed. Two independent judges evaluated the interview content in regards to emerging categories and obtained a Kappa index of 0.834. Results: Three categories emerged from the data: 1) Technical communication without emotional support, in which the information provided is composed of strictly technical information regarding the diagnosis, treatment and/or prognosis; 2) Technical communication, in which the information provided is oriented towards the technical aspects of the patient’s physical condition, while also providing psychological support for the patients’ subjective needs; and 3) Insufficient technical communication, win which there are gaps in the information provided causing confusion and suffering to the patient. Conclusions: Communication with emotional support contributes to greater satisfaction of chemotherapy patients. Practical implications: the results provide elements for the training of healthcare professionals regarding the importance of the emotional support that can be offered to cancer patients during their treatment.